PRIORITAS WASIAT DAN HUTANG DALAM WARISAN (PERBANDINGAN MAZHAB) - Abdul Syatar (Al-'Adl, 2018)
The three things that accompany a person when they want to leave the world are debt, will, and inheritance. In accordance with the rules in the text that govern the three problems. A person who wants or dies the top priority is to pay off his debts because the unresolved debt in the world is billed in the afterlife. Islamic inheritance law is a direct expression of sacred texts that are agreed upon. The manifest inheritance of a series of texts of sacred documents and obtaining high priority in its involvement as a fundamental principle phenomenon in the teachings of Islam. Debt should be prioritized rather than will because people who give loans may sue the deceased. While the testament is only giving (tabarru '). Repayment of debts for the deceased must be paid for the sake of prudence towards all of its debts, both in debt to Allah Almighty. as well as with fellow human beings.